FREQUENCY AND DETERMINANTS OF LEFT VENTRICULAR HYPERTROPHY IDENTIFIED ON ECHOCARDIOGRAPHY IN HYPERTENSIVE PATIENTS TO CARDIOLOGY DEPARTMENT OF DHQ TEACHING HOSPITAL MIRPUR AJK (The Research of Medical Science Review, 2025)
Objective: To observe the Frequency and Determinants of Left Ventricular Hypertrophy identified on Echocardiography in Hypertensive Patients presenting to Cardiology Department of DHQ Teaching Hospital Mirpur AJK Study Design: Cross Sectional Observational Study Study Duration: 06 months from Study Place: Divisional Head Quarter Hospital Mirpur Azad Kashmir Methods: Total 100 patients were observed in this study after taking informed written consent and ethical approval from hospital ethical review committee. BMI, blood pressure, sugar levels, age and gender of all the participants were recorded. In our study, 36 patients were male and 64 were females. All patients underwent 2D echocardiography to check for left ventricular hypertrophy, which was categorized as mild, moderate and severe. 2D echo was performed by same operator to remove biases. Results: In our study, we observed 100 participants, among them 64 were females and 36 were males. Only those patients were included who have hypertension. In our study, the mean age was 55±5 years, average random sugar levels were 170±10 and BMI was in the range of 25-33. The blood pressures were SBP 140±10mmHg-95±7mmHg. Our study revealed that out of 100 patients 83 (83%) had LVH, among those 83, 39 (46.9%) had mild LVH, 27 (32.5%) had moderate LVH and 17 (20.4%) had severe LVH. The most significant factor leading to LVH was uncontrolled hypertension (96.3%), second was obesity (44.5%) followed by age (36.1%). Conclusion: From our study, we can conclude that left ventricular hypertrophy has strong association with hypertension. Furthermore, we can also conclude that obesity and age in the setting of hypertension also have relationship with LVH.